THE INDONESIAN ARRANGEMENT OF ASSET FORFEITURE DRAFT AS REFORM EFFORTS IN RECOVERING STATE LOSSES DUE TO CORRUPTION: A COMPARATIVE STUDY OF UNITED STATES CODE - Sianipar, Ferry Agus; Sambas, Nandang; Yanto, Oksidelfa (YURIS: Journal of Court and Justice, 2024)
Corruption remains a pervasive challenge in Indonesia, undermining governance, economic development, and social justice. The Draft Law on Asset Forfeiture in Indonesia is an effort in reform to restore state losses caused by the crime of corruption. This is a comparative legal research which aims to compare the Draft Asset Forfeiture Law with the United States Code as a reference to assess compatibility with human rights. The findings of this research indicate that despite the fact that there have been numerous previous efforts and procedures from law enforcement to return assets under the criminal procedure law and other regulations, the judicial system is still insufficient to effectively address potential state financial losses due to the rampant corruption crimes in Indonesia. The Asset Forfeiture system, which shares similarities with the Asset Forfeiture principle in the U.S.C., has the potential to be abused and violates human rights and the basic Criminal Law principle of presumption of innocence, both in Indonesia and the United States. Therefore, it is necessary to improve the Draft Law on Asset Forfeiture with due regard to Human Rights, by placing the perpetrators of corruption on the Principle of the Highest Balanced Probability, and still adhering to the principles of the criminal process in accordance with basic criminal law.